Extremely strong DLAs at high redshift: gas cooling and H2 formation. Issue 4 (3rd January 2022) - Telikova, K N; Balashev, S A; Noterdaeme, P; Krogager, J-K; Ranjan, A
ABSTRACT: We present a spectroscopic investigation with the Very Large Telescope/X-shooter of seven candidate extremely strong damped Lyman-α absorption systems [ESDLAs, N (H i ) ≥ 5 × 10 21 cm −2 ] observed along quasar sightlines. We confirm the extremely high column densities, albeit slightly (0.1 dex) lower than the original ESDLA definition for four systems. We measured low-ionization metal abundances and dust extinction for all systems. For two systems, we also found strong associated H_2 absorption N(H_2) (cm^-2)=18.16± 0.03 and 19.28 ± 0.06 at z = 3.26 and 2.25 towards J2205+1021 and J2359+1354, respectively, while for the remaining five we measured conservative upper limits on the H_2 column densities of typically N(H_2) (cm^-2) 17.3 . The increased H2 detection rate (10–55 per cent at 68 per cent confidence level) at high H i column density compared with the overall damped Lyman-α population (∼5–10 per cent) confirms previous works. We find that these seven ESDLAs have similar observed properties as those previously studied towards quasars and γ-ray burst afterglows, suggesting they probe inner regions of galaxies. We use the abundance of ionized carbon at the excited fine-structure level to calculate the cooling rates through the C ii λ158 μm emission, and compare them with the cooling rates from damped Lyman-α systems in the literature. We find that the cooling rate distribution of ESDLAs also presents the same bimodality as previously observed for the general (mostly lower H i column density) damped Lyman-α population.